Helping Your Child Adjust to Child Care: Child Care 3 - Suzanna Smith (EDIS)
“Almost 13 million of the 18 million children younger than five years of age in the U.S. are in some form of regular childcare (Overturf Johnson, 2002). This means that millions of parents are finding ways to help their children adjust to being away from Mom or Dad and get used to a new routine and situation. Child development experts recommend a number of strategies, particularly in the early weeks of care.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, July 2012.